2016
DOI: 10.1016/j.bbadis.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Role of sphingomyelinase in mitochondrial ceramide accumulation during reperfusion

Abstract: Ceramide accumulation in mitochondria has been associated with reperfusion damage, but the underlying mechanisms are not clearly elucidated. In this work we investigate the role of sphingomyelinases in mitochondrial ceramide accumulation, its effect on reactive oxygen species production, as well as on mitochondrial function by using the sphingomyelinase inhibitor, tricyclodecan-9-yl-xanthogenate (D609). Correlation between neutral sphingomyelinase (nSMase) activity and changes in ceramide content were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…We found that acid (a) SMase was an upstream modulator of ceramide and CLC activation, leading to nephrotoxicity. In the pathogenesis of Wilson disease and heart disease, aSMase and ceramide accumulation have been shown to be involved in apoptosis of various causes (87)(88)(89)(90). Two studies indicated that ceramide, as a downstream product of activated aSMase, is crucially involved in the apoptosis of pulmonary epithelial cells and renal podocytes, indicating that ceramide perhaps not only mediates acute cellular stress but also participates in progressive tissue degeneration (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…We found that acid (a) SMase was an upstream modulator of ceramide and CLC activation, leading to nephrotoxicity. In the pathogenesis of Wilson disease and heart disease, aSMase and ceramide accumulation have been shown to be involved in apoptosis of various causes (87)(88)(89)(90). Two studies indicated that ceramide, as a downstream product of activated aSMase, is crucially involved in the apoptosis of pulmonary epithelial cells and renal podocytes, indicating that ceramide perhaps not only mediates acute cellular stress but also participates in progressive tissue degeneration (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides are a known cardiotoxin, contributing to heart disease by inducing cell death and inflammation. Ceramide activates cardiac cell death by accumulating in mitochondria of cardiomyocytes (43), resulting in either the formation of mitochondrial channels or general permeabilization (44). New evidence suggests that CBPs and CRPs may also play a role in cardiac cell death.…”
Section: Heart Diseasementioning
confidence: 99%
“…Diverse oxidative stresses induce cell apoptosis or necrosis and tissue damage via activation of SMases, resulting in sphingomyelin hydrolysis with ceramide generation. The accumulation of ceramide has been reported in multiple models of ischemia, including rat cerebral cortex and gerbil hippocampus ischemia [ 18 , 19 ], as well as in models of reperfusion injury, including artery occlusions in rat brain, liver, and heart [ 20 22 ]. In renal and cardiac IR injury models, activation of SMase and accumulation of ceramide were observed in the later phase of IR.…”
Section: The Sphingomyelin/ceramide Signaling Pathway and Irmentioning
confidence: 99%
“…With their own set of ceramide synthesizing and hydrolyzing enzymes, mitochondria serve as a specialized compartment of ceramide metabolism in cells. For example, SMases in mitochondria have been identified from zebrafish, mouse, and rat [ 20 , 49 , 50 ]. Purified ceramide synthase from bovine liver mitochondria showed higher activity than that from the ER [ 51 ].…”
Section: Mitochondrial Damage and Irmentioning
confidence: 99%
See 1 more Smart Citation